SOCIALIZATION AND DOOR TO DOOR GUIDANCE ON SIHALAL APPLICATION REGISTRATION PROCEDURES FOR CULINARY BUSINESS ACTORS TAMN VILLAGE - Vera Agustin; Pristiyono; Meisa Fitri Nasution (RADJA PUBLIKA, 2025)
The procedure for registering for Halal Certification through the SIHALAL application is an important issue because currently the development of culinary businesses in the regions continues to emerge in the lives of people whose areas are dominated by Muslims. Through halal product certification, it will help culinary business actors that the products marketed meet the requirements according to Islamic law. Therefore, this community service uses a collaborative mentor method, namely socialization about exploring information on the definition and meaning of halal and assistance in registering the SIHALAL application. The results of this community service activity certainly provide 1) benefits to culinary business actors by bringing guaranteed products, 2) building consumer trust, 3) helping the people of Asam Jawa Village, Sumber Rejo Hamlet, Torgamba District, South Labuhanbatu Regency about halal certification literacy and 4) ensuring that products and halal certification processes are in accordance with Islamic law mechanisms 5) introducing the SIHALAL application to the general public.